Fertility correlates with queen size and sperm quality in an ant - Lena-Marie Süß; Jan Oettler; Luisa Maria Jaimes-Nino (PLoS ONE, 2025)
Fitness can vary between individuals of the same population for reasons related to nutrient acquisition during development, but also to the quality of the mating partners. We focus on ant queens of Cardiocondyla obscurior to investigate the effects of female and male morphology and sperm characteristics on productivity. We monitored queens for 12 weeks after egg production started as a proxy for lifetime productivity, and found that larger queens are more productive, as commonly found in other insects, producing more workers and winged males. Sperm viability, but not sperm length, was positively correlated with female-biased sex ratios, pointing to a better insemination rate. The high correlation between sperm viability, male body size, and mandible size suggests strong selection for larger and stronger males. However, male competition for access to unmated queens in the maternal colony may result in a trade-off between male size and developmental time in this species.